Teachers’ Classroom Management Strategies in Creating Inclusive Learning Environments in Indonesian Primary Schools - Yanti Kahar; Muhaemin Muhaemin; Baderiah Baderiah (Universitas Cokroaminoto Palopo, 2026)
This study aimed to analyze teachers’ classroom management strategies in creating inclusive learning environments at SDN 60 Salubattang. The study focused on the implementation of inclusive education, classroom management strategies, and the supporting and inhibiting factors influencing inclusive learning practices. This research employed a qualitative case study design. Data were collected through classroom observations, semi-structured interviews, and documentation involving the principal, classroom teachers, subject teachers, students, and parents who were directly involved in inclusive learning activities. Data validity was ensured through triangulation, prolonged engagement, and member checking, while the data were analyzed using the interactive model of Miles and Huberman. The findings revealed that inclusive learning environments were created through integrated classroom management strategies, including differentiated instruction, adaptive classroom management, positive reinforcement, collaborative learning, and flexible assessment practices. These strategies worked together to accommodate students’ diverse academic abilities and learning needs, encourage active participation, and provide equal learning opportunities. Collaboration among teachers, parents, and school leaders also supported the implementation of inclusive learning, while positive peer interaction contributed to students’ social acceptance, cooperation, and classroom participation. However, the implementation of inclusive learning still faced several challenges, including limited educational facilities, insufficient instructional media, and limited teacher training related to inclusive education practices. This study concludes that teachers’ classroom management strategies are essential in strengthening inclusive learning environments in primary education and offers contextual insight into how inclusive classroom management is practiced in a suburban Indonesian primary school.